Examination of critical care pharmacist work activities and burnout. Issue 5 (22nd February 2021) - Smith, Susan E.; Slaughter, Aubrey A.; Butler, Sydney A.; Buckley, Mitchell S.; MacLaren, Rob; Newsome, Andrea Sikora
Abstract: Purpose: Critical care pharmacy services have progressed since their origination in the 1970s and have been supported by a position paper that categorized these services as fundamental (eg, provides drug information to the critical care team), desirable (eg, responds to resuscitation events in the hospital), and optimal (eg, publishes clinical research in peer‐reviewed journals). Burnout syndrome is a serious problem with far‐reaching consequences and may be heightened by the demanding nature of critical care. The purpose of this study was to explore the relationship between pharmacy services provided (fundamental, desirable, optimal) and the incidence of burnout syndrome among critical care pharmacists. Methods: A cross‐sectional survey was distributed via email to critical care pharmacists through a professional association listserv and included three areas of assessment: position and institution‐based characteristics, activities performed, and burnout. The primary outcome was the number of activities performed in each category and was compared between respondents who did and did not experience burnout using the Mann‐Whitney U test. Logistic regression was performed to characterize the relationship between activities performed and burnout. Results: In total, 211 pharmacists (14.5%) completed the survey. Sixty percent (n = 128) experienced burnout and performed a median of 13 (interquartile range [IQR] 7‐15) fundamental (of 18 assessed), 11 (IQR 4‐13) desirable (of 16 assessed), and 6 (IQR 5‐8) optimal (of 12 assessed) activities. In logistic regression, performing desirable activities was associated with higher risk of burnout while performing optimal activities was associated with lower risk of burnout. Conclusions: Over half of critical care pharmacists experienced burnout. The performance of optimal activities was associated with reduced burnout. It is possible that higher level, higher yield activities increase personal engagement and decrease burnout.